Comparative Analysis of Arabic and English Noun Usage in Gender Linguistics - Safarova Zarnigor (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Gender linguistics is an area of study that delves into how languages express gender within their structures. This article seeks to explore and contrast the mechanisms of gender representation within noun usage in Arabic and English, elucidating the cultural, historical, and structural influences that underpin these systems. Furthermore, the article aims to offer insights into the multifaceted nature of gender representation within language. By examining and contrasting these systems, the analysis provides a deeper understanding of the role of gender within linguistic frameworks, enriching our comprehension of gender linguistics within various cultural and linguistic contexts.